Planning strategy through reduce cognitive load of secondary school students: Brief metacognitive development analysis - Jatmiko, Jatmiko; Retnawati, Heri; Rohman, Arif (Edelweiss Applied Science and Technology, 2025)
Stages of the learning process sometimes reveal conceptual errors found in the information obtained by students that has been conveyed by teachers. Metacognition is able to provide monitoring strategies for students' thinking stages; therefore, they are able to describe thinking strategies, the results of their thinking, and the stages of the learning process. Metacognition plays a significant role, particularly in solving mathematical problems. This research is targeted at identifying planning strategies to reduce the cognitive load of metacognitive strategies in the mathematics learning model, which are considered dominant and linear among secondary high school students. The number of stages of metacognitive development includes identification of what you know, talking about thinking, keeping a thinking journal, planning and self-regulation, reporting back on thought processes, and self-evaluation. This research and development use the ADDIE steps, which cover analysis, design, development, implementation, and evaluation. The subjects of the research include 8th grade junior high school students in the City of Kediri. Findings indicate that metacognition is an individual's process of thinking related to thinking in order to build strategies for solving problems. Metacognition is identified through activities that cover planning how to approach learning tasks, monitoring abilities, and evaluating plans in order to carry out tasks. Research findings revealed the syntax of the worked example-metacognition learning model in mathematics learning, which includes the introductory stage, exploration, controlled practice, and evaluation. The worked example-metacognition learning model in mathematics learning is considered feasible by experts and practitioners. The worked example-metacognition learning model in mathematics learning is considered practical by observers and students, and it is effective in reducing cognitive load and improving students' improvisation metacognitive skills.